Laparoscopic Appendectomy Is Safe. Issue 3 (June 2015) - Sohn, Maximilian; Hoffmann, Maria; Hochrein, Alfred; Buhr, Heinz J.; Lehmann, Kai S.
<x xml:space="preserve">Abstract</x> Purpose: Surgical-site infections (SSIs) and intra-abdominal abscesses (IAAs) are the most frequent complications of appendectomy. The role of laparoscopy in the treatment of appendicitis remains controversial concerning the complication rate. The aim of this retrospective cohort study was to compare open and laparoscopic appendectomy for SSI and IAA. Methods: All patients undergoing appendectomy between January 1, 2007 and May 31, 2010 were included in the study. Perioperative data and data on postoperative complications were collected from patient files. A questionnaire was used to assess complications after discharge. Main outcome parameters were SSI and IAA. Open appendectomy (OAG) and laparoscopic appendectomy (LAG) were compared with univariate and multivariate analyses for the outcome parameters. Results: Four hundred thirty patients were included in the study. SSI (all: 10.6%, OAG: 11.7%, LAG: 7.5%, P=0.293) and IAA (all: 2.8%, OAG: 2.4%, LAG: 3.8%, P=0.506) were not significantly different between OAG and LAG. Risk factors for SSI were age (P=0.003), body mass index (P=0.017), ASA score (P=0.001), the intraoperative grade of inflammation (P=0.004), and the histologic grade of inflammation (P=0.015). The only risk factor for IAA was the intraoperative grade of inflammation (P=0.028). ASA score (odds ratio: 1.992, P=0.032) and the intraoperative grade of inflammation (odds ratio: 1.573, P=0.006) remained significant in the multivariate analysis for SSI. Conclusions: A higher ASA score correlates with SSI. A higher grade of intraoperative inflammation correlates with SSI and IAA. Laparoscopy has no impact on SSI and IAA in appendectomy.